TINGKAT PENGETAHUAN IBU PRIMIGRAVIDA TENTANG TANDA-TANDA PERSALINAN NORMAL DI RSUD KEBUMEN 2010 - diah hapsari; Basirun -; hastin ika indriyastuti (Jurnal Ilmiah Kesehatan Keperawatan, 2010)
In order to prepare the baby well, primigravida mother should know the sign of pregnancy first. There was 3884 baby birth in Kebumen District General Hospital of the year 2009 from primigravida mothers. 1486 of them always checked their pregnancy to the maternity clinic. Since, there is a lot of primigravida pregnancy, a primigravida mother have to prepare how to get a normal baby birth. The general goal of this research is identifying the level of primigravida mother’s the knowledge about the birth sign in Kebumen District General Hospital. The specific goal of this research knows the level of primigravida mother’s knowledge abaut the brith signs in Kebumen District General Hospital. This research used descriptive and explorative research method. The intensity of primigravida pregnant woman of the research. Purposive sample is the sample research and the level of primigravida mother’s the knowledge about  the normal birth indications. level of primigravida mother’s knowledge about the normal birth signs in Kebumen District General Hospital of the year 2010, is 91,7%. The least is 8,3%, average level (junior and senior high school) of 64,6%, while the  least level come from those who graduated from elementary school in 18,8%. The level of Primigravida mother’s knowledge in Kebumen  District General Hospital about the normal birth sign from enough to great level every month is about 91,7% and the least one from lack level of knowledge is about 8,3%.   Key words: level of primigravida mother’s knowledge, the normal brith signs.